New Traders’ Mood when using Trading Online Application in Universitas Multimedia Nusantara - Lisa Oviani; Raymond Sunardi Oetama (IJNMT (International Journal of New Media Technology), 2018)
Trading online have a brief history of success all due to Internet. However, beginners find some difficulties to make profit. One of the reasons is their moods. This study is focused to explore their moods. Some moods are found has relation with the trading online. Avoiding loss in trading online, some moods should be controlled first before they start trading. Index Terms— Trading Online, Foreign Exchange